Wales and the Welsh in the Middle Ages : essays presented to J. Beverly Smith - Griffiths, Ralph A. (Ralph Alan), 1937-; Schofield, Phillipp R., 1964-; Smith, J. Beverley (University of Wales Press, 2011)
This is a major contribution to the study of medieval Wales by a group of outstanding British historians, writing in honour of one of Wales's most distinguished scholars and the biographer of Prince Llywelyn ap Gruffudd. The essays reflect exciting trends in the study of both Wales and the Middle Ages, including church building, chronicle writing, the comparative history of the law, and valuable reassessments of town life and the implications of the Edwardian conquest of Wales.